Thermoluminescence based personnel neutron dosimetry study of LiMgBO3:Dy3+. Issue 12 (15th August 2020) - Sen, Meghnath; Shukla, Rakesh; Sathian, V.; Kulkarni, M.S.; Tyagi, A.K.
Abstract: The present paper reports the thermoluminescence (TL) based personnel neutron dosimetry studies of LiMgBO3 : Dy 3+ phosphor. It offers the great advantage of being a near tissue equivalent material with Zeff  = 9.1. Also, the presence of both Li and B in the host matrix directly induce TL signal for neutrons. This is highly advantageous over CaSO4 : Dy based TL neutron dosimeters where it requires to mix some thermal neutron sensitive species with the host matrix to induce neutron response. LiMgBO3 : Dy 3+ was synthesized by sol gel method and its structural characterizations were done by XRD, SEM and EDS techniques. TL upon irradiation with neutrons showed the glow peak at ~140 °C (413K). TL response up to 200 mSv of neutron dose showed very good linearity with adj. R 2  = 0.998. 30% borated rubber discs were successfully utilised for the segregation of the gamma dose from the total dose in the mixed field (neutron + gamma) environments. The minimum detectable dose of the material was found to be 27.5 μGy and 2.7 μSv for gamma and thermal neutrons respectively. The TL sensitivity of LiMgBO3 : Dy 3+ for neutron and gamma radiation is 0.6 times and 0.3 times respectively with respect to that of standard TLD-100 [LiF: Mg, Ti] material. The proposed LiMgBO3 :Dy 3+ was also found to have better n/γ dose discrimination capability as compared to the commercially available TLD-100 material [LiF: Mg, Ti]. The kinetic parameters (viz. E, b and s) of the neutron irradiated TL glow peak were determined by Chen's peak shape and by variable heating rate methods.